African models for transnational river basin organizations in Africa: An unexplored dimension - Merrey, Douglas J. (Water Alternatives, 2009)
One of the many legacies of colonialism in Africa is the multiplicity of river basins shared by two or more – and often far more – countries. Since changing national boundaries is not an option, African governments have no choice but to develop transnational institutions for developing shared water resources. Therefore, one finds a plethora of bilateral and multilateral committees, commissions, and authorities intended to facilitate agreements for infrastructural investments, management of water flows (quantity and quality), and response to disasters, especially floods. These efforts are supported by – indeed often, at least behind the scenes, driven by – western and international development partners. With few exceptions, the results to date are not impressive, as governments drag their feet on ratifying or implementing agreements and investing in creating the necessary institutional infrastructure, and donors’ funds go unspent because such agreements are conditions precedent for investment. Despite the work done by many international and local non‐government organisations (NGOs) as well as some governments, hardly any of the residents of African river basins are aware of these commissions. All of them are based on organisational models derived from western experiences and governing principles and are created by inter‐governmental agreements. The citizens residing in the basin are rarely consulted. In some cases, powerful national hydraulic bureaucracies seek to control the process in an effort to gain leverage over infrastructural investments. There is a body of literature seeking to explain the ineffectiveness of transnational river basin management to date, largely based on political science, sociology and economics. Some but not all observers are concerned with the degree of democracy in the political process. This paper addresses a dimension that has received very little attention and therefore complements the existing literature. It explores the hypothesis that transnational river basin management institutions will achieve a higher degree of legitimacy and effectiveness in the long run if they are based on African institutional models rather than pursuing the current approach of imposing external models. This assumes the existence of local African indigenous models or principles that can be adapted to such large‐scale hydraulic institutions. The paper argues this may indeed be the case though more detailed research is needed to document them, and a creative consultative political process would be needed to build on these foundations.